Huellas de identidad en la danza Choqela: (Puno, Perú) - Gudemos, Mónica; Apaza Ticona, Jorge (Notas de Antropología de las Américas, 2023)
In this paper we address the polysemic nets of identity appropriation of Aimaradances in Puno (Peru). We analyze the tense relationship established between thediscourses installed by the structures of political power and the strategies of Aimaracommunities of the region to sustain these performances as elements of socialcohesion. We focus our argumentative observations on the Choqela dance, rituallylinked to the vicuña hunting or chaccu.